PEMERIKSAAN TEKANAN DARAH PADA PROGRAM PEMBANGUNAN KESEHATAN MASYARAKAT DESA (PPKMD) - Muhammad Hadi Sulhan; Tantri Puspita; Mamay; Gina Nafsa Mutmainna; Sri Yekti Widadi (Jurnal Pengabdian Masyarakat DEDIKASI, 2020)
Hypertension is often called the "silent killer" because often people with hypertension go for years without feeling any disturbances or symptoms. Without realizing it, patients experience complications in vital organs such as the heart, brain or kidneys. This activity uses a direct inspection approach to the residents present. The target of community service is residents who are in RT 02/RW 02 Darmaraja Village. Checking blood pressure using a digital sphygmomanometer/tensimeter. The participants who took part in the activity were 16 (sixteen) elderly participants. From this community service activity, it can be concluded that health education about hypertension is needed and routine and ongoing health checks obtained from the results of activities including hypertension as much as 75% or 12 (twelve) residents, 6.25% or 1 (one) citizen. suffering from heart disease, 6.25% or 1 (one) resident suffering from gout, 6.25% or 1 (one) resident suffering from gastritis/stomach, 6.25% or 1 (one) resident suffering from diabetes.